Cocoa Flavonoids Reduce Inflammation and Oxidative Stress in a Myocardial Ischemia-Reperfusion Experimental Model - Sajeela Ahmed (Antioxidants, 2020)
Consumption of flavonoid-rich nutraceuticals has been associated with a reduction in coronary events. The present study analyzed the effects of cocoa flavonols on myocardial injury following acute coronary ischemia-reperfusion (I/R). A commercially available cocoa extract was identified by chromatographic mass spectrometry. Nineteen different phenolic compounds were identified and 250 mg of flavan-3-ols (procyanidin) were isolated in 1 g of extract. Oral administration of cocoa extract in incremental doses from 5 mg/kg up to 25 mg/kg daily for 15 days in Sprague Dawley rats (n = 30) produced a corresponding increase of blood serum polyphenols and become constant after 15 mg/kg. Consequently, the selected dose (15 mg/kg) of cocoa extract was administered orally daily for 15 days in a treated group (n = 10) and an untreated group served as control (n = 10). Both groups underwent surgical occlusion of the left anterior descending coronary artery and reperfusion. Cocoa extract treatment significantly reversed membrane peroxidation, nitro-oxidative stress, and decreased inflammatory markers (IL-6 and NF-kB) caused by myocardial I/R injury and enhanced activation of both p-Akt and p-Erk1/2. Daily administration of cocoa extract in rats is protective against myocardial I/R injury and attenuate nitro-oxidative stress, inflammation, and mitigates myocardial apoptosis.